Screening optimum reference genes for quantitative real-time polymerase chain reaction analysis in invasive apple snail, Pomacea canaliculata under different conditions - Ya-Wen Chang; Han-Di Long; Ran Wei; Zhen-Jun Sun; Guo-Xian Zha; Cheng-Dong Wu; Hong-Fang Xie; Jie Hu; Yu-Zhou Du (Molecular Biology Reports, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Effects of confluence angle and ice coverage on morphodynamics in ice-covered river confluences: insights from laboratory experiments - Zhiwei Li; Haokun Feng; Cheng Liu; Keyao Han; Bin Sun; Gang Chen; Feifei Wang (Advances in Water Resources, 2026)

Melatonin breaks the superoxide-driven autocatalytic loop to achieve UV-stable SnPb perovskite solar cells - Sirui Han; Mingzhe Zhu; Jiakang Zhang; He Sun; Cheng Peng; Wei Tan; Siyu Song; Ruotong Kang; Chenyang Xia; Zhongmin Zhou (Chemical Engineering Journal, 2026)

A composite Sleep Thermal Health Index (STHI) framework for sleep-period thermal health under warm nights with PLS-SEM-based composite pathway analysis - Zhaohan Bai; Yunsong Han; Qi Dong; Shuangyu Xu; Rui Sun; Yongheng Jia; Cheng Sun (Building and Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Exogenous calcium modulates oxalic acid metabolism via repression of LcAAE3 and mediates calcium accumulation in litchi pericarp and fruit pedicel - Dong-Cheng Li; Zhi-Qun Zhong; Teng-Kai Chen; Yi-Tong Liu; Yue-Han Sun; Hui-Cong Wang; Ren-Fang Zeng; Xu-Ming Huang (Journal of Plant Physiology, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Macrophyte-to-algae transition: Suspended particulate matter mediates the bioavailability and retention of heavy metal(loid)s in the sediment - Wenxuan Han; Yiheng Du; Xue Sun; Zhaode Wang; Lei Zhang; Xiaozhi Gu; Hongbin Yin; Cheng Liu (Journal of Environmental Chemical Engineering, 2026)

Artificial intelligence-enabled machine olfaction for volatile profiling and food quality decision-making - Yitian Gao; Jun-Hu Cheng; Han Wang; Yuandong Lin; Jinhua Wang; Da-Wen Sun (Food Chemistry, 2026)

Priority control of potentially toxic elements in urban park soils through integrated source apportionment and health risk assessment - Xiangtian Man; Jian Sun; Xingnian Ren; Mengli Chen; Cheng Yang; Ruxin Yang; Ailian Li; Junfang Cui; Han Zhang (Environmental Geochemistry and Health, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

Cell-Type-Specific Calibration of Mitochondrial Ubiquitination in Stem Cell Fate Decisions - Hao-Cheng Liu; Si-Yuan Chen; Nan-Nan Yu; Mei-Hua Jin; Hu-Nan Sun; Ying-Hao Han (Stem Cell Reviews and Reports, 2026)

Neuro-symbolic framework for multi-USV coordination: COLREGs-compliant and energy-efficient smart navigation - Shuai Huang; Yi-Feng Chen; Mao-Yuan Sun; Jia-Ning Gao; Yu-Han Zhou; Jing-Wen Zeng; Cheng-Chen Wang; Ya-Ze Han; Yang Xiong (Frontiers in Marine Science, 2026)
Introduction Coordinating multiple unmanned surface vehicles (USVs) in coastal waters requires simultaneous consideration of COLREGs compliance, real-time response, energy efficiency, fault tolerance, and semantic scene understanding. Existing approaches typically address only part of this problem and provide limited support for integrated fleet-level coordination. Methods This paper proposes NSC-Marine, a neuro-symbolic framework that conceptually addresses these coupled constraints. It combines multimodal causal perception, LLM-based rule reasoning, energy-aware motion planning, and distributed fault reconfiguration within a dual-rate control architecture. To improve deployment safety, semantic reasoning is used to generate structured constraints, while low-level motion execution remains under deterministic planning and control. Results The framework is evaluated strictly within a physics-based simulation environment with approximately 70% overall fidelity, involving 1,000 trials of 20–100 USVs under Beaufort Scale 3–5 conditions. Under these simulated conditions, NSC-Marine achieves 88.7% ± 2.3% COLREGs compliance, 82.3% mission success under compound faults, and 13.6% energy reduction relative to the RLCA baseline, while maintaining a 320 ms critical-path latency. Discussion These metrics reflect an idealized simulation baseline and must not be generalized to physical deployment readiness. Real-world performance remains unvalidated, and staged hardware-in-the-loop testing and field trials are required to characterize the system’s actual behavior under physical disturbances.

Intelligent optimization of soil conditioning schemes based on earth pressure balance shield tunnelling data - Xin Wang; Wen Zhao; Jialong Li; Jianyong Han; Cheng Cheng; Qian Bai; Dazeng Sun (Tunnelling and Underground Space Technology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Long-term aging of oxychar and biochar: structural, adsorptive, and microbial transformations - Cheng Ji; Shutao Wang; Man Zhang; Hang Sun; Qinggang Meng; Kexin Zhao; Yifan Li; Shiming Su; Bing Han; Wei Liu (Fuel, 2026)

Characterizing above- and below-ground biomass of alpine basin-scale grassland on Qinghai-Tibet Plateau through climate, soil and topography drivers - Xuyang Sun; Jintao Liu; Zhenghong Yu; Zhen Cheng; Ping Huang; Xiaole Han; Hu Liu (CATENA, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Distinctive role of cerium oxide and MXene in enhancing the hot corrosion resistance of NiCu composite coatings in strong acidic and saline environments - Xingtao Cheng; Kaijun Wei; Qing Yuan; Yi Sun; Shijun Xu; Han Liu; Quangang Chen; Xiangshan Hou; Longbo Luo; Yi He (Chemical Engineering Journal, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

A newly designed retaining wall model apparatus for investigating lateral soil arching effect under controlled wall deformation - Cheng-Shuang Yin; Han-Lin Wang; Xiang-Shen Fu; Yue-Hui Sun; Xiao-Hu Zhang; Marawan Shahien (Transportation Geotechnics, 2026)

Risk assessment and exposure patterns of hydroxypolycyclic aromatic hydrocarbons in elderly population: Insights from urinary metabolite levels and dietary habits - Yafei Gao; Biwen Wang; Liting Hua; Juanhua Li; Junqi Liu; Yang Peng; Lu Cheng; Hongkai Zhu; Hongwen Sun; Han Li; Hongzhi Zhao (Journal of Environmental Sciences, 2026)

Exploration of chicken lung antioxidant peptides modified by plastein reaction: Purification, identification and molecular docking - Jingwen Jia; Siyu Cheng; Lisheng Li; Tian Chen; Na Xu; Xiaomei Sun; Yun Bai; Xinglian Xu; Minyi Han (Food Bioscience, 2026)

Spatial compartmentalization of ultrafine Ni nanoparticles within nanoporous carbon spheres for rapid magnesium hydrogen storage - Haotian Sun; Wanqiang Liu; Yufei Liu; Wenfeng Qiao; Qingyun Shi; Jian Cai; Dongming Yin; Hao Wang; Chunli Wang; Qingshuang Wang; Ying Wang; Yong Cheng; et al. (Chemical Engineering Journal, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Multimodal evidence of temperature and sex effects on sleep: sleep physiology, sleep quality, and next-day performance - Zhaohan Bai; Yunsong Han; Qi Dong; Shuangyu Xu; Rui Sun; Yongheng Jia; Cheng Sun (Building and Environment, 2026)

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Structural optimization of natural plant products: Construction and insecticidal activities study of eugenol's derivatives - Wen Zhang; Xiao-Han Zhang; Li-Hong Sun; Cheng-Yuan Liu; Wen-Hui Zhang; Yi-Wen Huang; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Pesticide Biochemistry and Physiology, 2026)

Efficient sampling the microbiome in human exhaled bioaerosols: A comparison of condensation-based and wet-wall cyclone techniques - Han Gao; Mengqing Cheng; Weihao Li; Manman Lv; Yemin Han; Haotian Yu; Xinping Xu; Zuhong Lu; Dianhuai Meng; Longhua Sun; Quanjun Liu (Journal of Environmental Chemical Engineering, 2026)

Ginseng polysaccharide-based hydrogel loaded with MnO2 nanosheets and rhEGF synergistically regulates oxidative stress, macrophage polarization, and angiogenesis for accelerated diabetic wound healing - Chunxue Zhang; Tingting Liu; Cuiyan Han; Cheng Yuan; Jiaqi Sun; Jing He; Xueting Yang; Xiaoyu Sui (Chemical Engineering Journal, 2026)

Co-application of humic acid and phosphorus fertilizer enhances soil carbon stability and phosphorus availability in coastal saline paddy fields - Chuanming Ma; Zhaohui Liu; Ben Cheng; Jinkai Han; Lening Zhang; Zeqiang Sun; Shenglin Liu; Shirong Zhang; Xiaodong Ding (Plant and Soil, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

System-dependent effects and mechanisms of microplastics/nanoplastics on nitrogen and phosphorus removal from wastewater treatment and N2O emission - Tong Wu; Shuai-Hang Wang; Ping Fang; Cheng-Xin Chen; Jie Ding; Ying He; Han-Jun Sun; Meng-Qi Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2026)

Long‐lived subsurface anticyclonic eddy enhances microbial diversity and vertical niche partitioning - Ying Wang; Zhaomin Han; Lei Wang; Peng Cheng; Dapeng Xu; Bangqin Huang; Ping Sun (Limnology and Oceanography, 2026)
Subsurface anticyclonic eddies (SAEs) reshape ocean stratification and nutrient–light regimes, yet their microbial and biogeochemical impacts remain poorly resolved. We combined CTD‐ADCP hydrography, nutrient profiles, microscopy and flow‐cytometry, and 18S/16S rRNA transcript sequencing to examine a long‐lived SAE in the northern South China Sea. The lens‐shaped eddy featured a strong velocity core (maximum 0.46 m s −1 at 90 m) and a deepened euphotic zone from exterior reference to edge to center (107.9 → 117.9 → 124.5 m). Depth‐integrated chlorophyll‐ a (25–150 m) was higher inside the eddy (19.7 mg m −2 ) than at reference waters (18.2 mg m −2 ), peaking at the center (20.8 mg m −2 ), indicating subsurface intensification of autotrophic biomass. Alpha‐diversity enhanced within the eddy, especially at its edge, while vertical turnover of protistan and bacterial assemblages exceeded center–edge differences, contrasting with surface‐intensifying anticyclonic eddies that often homogenize communities. Distance‐based redundancy analyses identified water mass, nutrient, viral, bacterial, and nanoflagellate gradients as key correlates of community structure, reflecting light‐nutrient colimitation modulated by top‐down control. Ecotype‐resolved patterns supported this framework that high‐light Ostreococcus tauri declined, whereas low‐light Prochlorococcus MIT9313 was ~ 5‐fold enriched just above the core and toward the center. Protist–bacteria co‐occurrence network formed depth‐ and edge‐specific modules and hub taxa included protist Stramenopiles, free‐living Alphaproteobacteria and particle‐associated Deltaproteobacteria. Collectively, the deepened euphotic zone and elevated subsurface chlorophyll‐ a , together with spatially structured community assembly, demonstrate that the eddy functions as a localized biogeochemical reactor enhancing subsurface productivity and microbial recycling in oligotrophic waters—linking eddy physics to ecosystem function.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Organic matter cycling reveals escalating algal blooms and accelerated mineralization in a macrophyte-dominated cold-arid eutrophic lake - Fengrui Zhang; Wenxuan Han; Xue Sun; Zhaode Wang; Lei Zhang; Qiushi Shen; Haijin Lan; Bingfa Chen; Hongbin Yin; Cheng Liu (Water Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

POINT: a web-based platform for pharmacological investigation enhanced by multi-omics networks and knowledge graphs - Zihao He; Liu Liu; Dongchen Han; Kai Gao; Lei Dong; Xiaoning Qi; Dechao Bu; Peipei Huo; Zhihao Wang; Xuan Fan; Jingming Sun; Shuangshuang Lei; et al. (Science Bulletin, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

An aerosol-scaled QMRA based on viral surrogates for indoor airborne pathogen risk assessment - Han Gao; Mengqing Cheng; Haotian Yu; Tian Wen; Xinping Xu; Longhua Sun; Zuhong Lu; Quanjun Liu (Building and Environment, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Deciphering the butylated hydroxytoluene dissolution behavior in solid-liquid systems through coupled experimental and molecular dynamic simulation approaches - Xing Wu; Xiaowei Cheng; Shiyu Sun; Jixu Ni; Yuan Han; Mengwen Qu; Baoshu Liu; Hua Sun (Food Chemistry, 2026)

Associations of urinary environmental phenols with obesity and lipid metabolism in children and adolescents: The expanded Chinese National Human Biomonitoring (CNHBM) project - Nan Jiang; Qi Chen; Beijing Cheng; Ke Meng; Jia Wang; Tianlin Li; Han Chen; Yinghao Liao; Hong Sun; Ran Liu (Environmental Research, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Immobilization of multiple hazardous metals in fly ash waste by enzyme-induced carbonate precipitation - Zishen Fang; Hengxing Wang; Liang Cheng; Jiangshan Li; Lijun Han; Linchang Miao; Xiaohao Sun (Journal of Environmental Management, 2025)

Rapid in situ growth of ZIF on diatomite toward high-selectivity adsorption of sulfonic anionic dyes - Jiapeng Li; Qiushi Jiang; Lianzhi Sun; Jingjing Zhang; Zhaolian Han; Zhihui Dong; Chunli Zhao; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2025)

Regulatory effect of Chinese Baijiu on gut microbiota and host metabolism - Cheng Fang; Bowen Wang; Yehui Han; Xiaojiao Zheng; Wei Jia; Jinyuan Sun; Yan Xu (Food Research International, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

The relationship between the dynamic trajectory of inflammatory markers in VA-ECMO patients and the 28-day survival rate, as well as mediating causal analysis - You Zhou; Zhi Cheng; Liqun Sun; Jiayan Han; Suhui li; Xin Wang; Leiming Xu (Inflammation Research, 2025)

Memristor-based RDBO-CNN circuit design and application of image multi-classification recognition - Gaoyong Han; Guanxiang Cheng; Yanfeng Wang; Junwei Sun (Cognitive Neurodynamics, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

Operational optimization for electric heat pump clusters based on demand response considering user comfort - Gao Xiaozhi; Chang Pengyu; Zhao Qiyang; Lin Hsiung-Cheng; Sun Huiqin; Xu Shiwei; Xiao Han (Energy and Buildings, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Experimental study of localized hydro-thermal-mechanical coupling characteristics of unsaturated silt under step-freezing conditions - Yu-zhi Zhang; Cheng-yan Li; Meng Wang; Yi-han Cui; You-cheng Sun (Cold Regions Science and Technology, 2025)

Aging or degradation? Transformation mechanisms of microplastics in soil environments - Xingyu Zhong; Liyuan Qiang; Jinping Cheng; Zhihang Sun; Huibing Hu; Han Liu; Ruoyu Zhang (Applied Soil Ecology, 2025)

Metal-free heterogeneous electro-Fenton with solid polymer electrolytes: A novel self-supporting system for PPCPs decontamination - Jilong Wang; Qi Xiang; Ye Han; Zeyu Ma; Wei Cheng; Jie Sun; Shaobin Wang (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Ultrarobust eutectogels with nanophase separation structure for self-damping pressure sensing - Zong-Ju Chen; Yu-Qiong Sun; Zi-Han Zhao; Li-Jia Pan; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Pseudomonas bambusae sp.nov., an Aniline Blue-Decolorizing Bacterium Isolated from Decaying Round Bamboo Culms - Xiao-Long He; Jia-Yan Wang; Jin-Jia Liang; Cheng-Jing Ren; Xin-Yi Guo; Wen-Jie Ke; Min Wu; Hong-Zheng Liu; Min Jin; Fang-Li Sun; Shuai-Bo Han (Current Microbiology, 2025)

Co-fermentation of Astragalus membranaceus residues, Licorice residues, and Corni Fructus residues for the production and optimization of Ganoderma lucidum metabolites based on data networks and fermentation kinetics models - Xiaomei Sun; Yitong Qi; Mengtao Cheng; LiYing Zhang; Chunchao Han (Clean Technologies and Environmental Policy, 2025)

A novel multifunctional suction-controlled apparatus for investigating tensile strength of unsaturated soils - Xiang-Shen Fu; Han-Lin Wang; Ren-Peng Chen; Cheng-Shuang Yin; Yue-Hui Sun; Xiao-Hu Zhang; Daniel Dias (Transportation Geotechnics, 2025)

Chloroinconazide inhibits Pseudomonas syringae pv. tabaci causing tobacco wildfire disease by directly destroying bacteria and inducing oxidative damage - Fengwei Li; Ke Wang; Xin Zhu; Weina Liu; Yanlin Wu; Dashu Lv; Yanjing Han; Xiangchuan Wang; Daoquan Cheng; Tao Chen; Chen Xu; Xianchao Sun (Pesticide Biochemistry and Physiology, 2025)

Flotation performance and characterization evolution of bastnaesite in hydrogen mineral phase transformation process - Shaokai Cheng; Wenbo Li; Hong Peng; Yuexin Han; Peng Gao; Yongsheng Sun (Minerals Engineering, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A cyber-attack detection based on time-delay mutual information analysis - Fangyuan Ma; Cheng Ji; Jingzhi Rao; Chengyu Han; Jingde Wang; Wei Sun (Process Safety and Environmental Protection, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Livestock excreta facilitate invasive weed establishment and dominance in pastures through physical niche creation and nutrient pulses - Qihong Yuan; Xincheng Li; Cheng Zhang; Tingting Tao; Han Y.H. Chen; David Johnson; Zhiwei Zhong; Wei Zhang; Shaoli Zhong; Xiao Sun (European Journal of Agronomy, 2025)

Laboratory-Scale Study of Hydraulic Fracture Interaction with Natural Fracture Networks - Bo Sun; Yuanfang Cheng; Zhenhai Liu; Mingyu Xue; Junchao Yang; Chuanliang Yan; Zhuyu Zhao; Zhongying Han (Geotechnical and Geological Engineering, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Cerium oxide nanoparticles ameliorate Arabidopsis thaliana root damage under UV-B stress by modulating the cell cycle and auxin pathways - Cheng Sun; Chen Zhao; Guohua Wang; Rong Han (Protoplasma, 2025)

Neural Networks and Chemical Messengers: Insights into Tobacco Addiction - Jieping Sun; Qingqing Lv; Jinghan Dang; Mengzhe Zhang; Qiuying Tao; Yimeng Kang; Longyao Ma; Bohui Mei; Weijian Wang; Shaoqiang Han; Jingliang Cheng; Yong Zhang (Brain Topography, 2025)

Mechanisms of SIRT1/SIRT3-mediated reduction of mitochondrial regeneration and inflammatory response in diabetic cerebral ischemia-reperfusion injury - Cheng Xin; Ouya Liu; Miao Sun; Ping Han; Xiaowen Li; Qingfeng Niu; Nenghong Ma; Xiao Yang; Changchun Hei; Ping Liu (Metabolic Brain Disease, 2025)

Inhibition of JAK2/STAT3 by pacritinib synergizes with chemotherapy in esophageal carcinoma - Lan Han; Yinyin Sun; Kai Yang; Cheng Long (Toxicology in Vitro, 2025)

Learning-infused optimization for evolutionary computation - Kun Bian; Juntao Zhang; Hong Han; Jun Zhou; Yifei Sun; Shi Cheng (Swarm and Evolutionary Computation, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Discovery of Active Ingredient of Yinchenhao Decoction Targeting TLR4 for Hepatic Inflammatory Diseases Based on Deep Learning Approach - Sizhe Zhang; Peng Han; Haiqing Sun; Ying Su; Chen Chen; Cheng Chen; Jinyao Li; Xiaoyi Lv; Xuecong Tian; Yandan Xu (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Akebia trifoliata extracts attenuate liver injury via gut–liver axis in a murine model of nonalcoholic fatty liver disease with low-grade colitis - Xiaoya Wang; Han Chen; Weifeng Zhu; Zhongliang Wang; Yao Pan; Yong Sun; Hua Xiong; Junmei Zhou; Wenliang Cheng; Kejun Cheng (Food Research International, 2025)

Integration of microbiomics and metabolomics reveals energy metabolism imbalance in crucian carp (Carassius auratus) under saline-alkaline exposure - Lin Han; Wenzhi Liu; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Mechanism of blocking the glutamate pathway to exacerbate oxidative stress, ammonia toxicity and metabolic disorders in crucian carp (Carassius auratus) under saline-alkaline exposure - Wenzhi Liu; Lin Han; Fangying Yuan; Qianwen Liu; Hongyu Cheng; Xiaofeng Jin; Yanchun Sun (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Thickness-dependent topological phases and flat bands in rhombohedral multilayer graphene - Hanbo Xiao; Cheng Chen; Xin Sui; Shihao Zhang; Mengzhao Sun; Han Gao; Qi Jiang; Qiao Li; Lexian Yang; Mao Ye; Fangyuan Zhu; Meixiao Wang; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Development of a Mixotrophic Strategy for Efficient Cultivation of a Coccolithophore, Chrysotila roscoffensis - Luyao Zhang; Zhichao He; Yan Sun; Jian Li; Pengfei Cheng; Nicolas Spiros Agathos; Chengxu Zhou; Lin Zhang; Jichang Han (Journal of Ocean University of China, 2025)

Rice THIN CULM 4 (TC4) modulates culm strength by regulating morphology, structure, and development - Ran Zhou; Chenbo Huang; Xiaoxia Wen; Zhihao Sun; Wei Dong; Yuyu Chen; Nuan Huang; Han Zhang; Haihan Su; Yanhui Li; Zequn Peng; Yingxin Zhang; et al. (Plant Science, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An electrically activable nanochip to intensify gas-ionic-immunotherapy - Gang Wang; Jingrui Li; Shumin Sun; Yuqi Yang; Zhihui Han; Zifan Pei; Liang Cheng (Science Bulletin, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

A GAN-based cyclic iterative unsupervised change detection network - Guanghui Yang; Xianwei Han; Lei Zhang; Wei Gao; Yunliang Hu; Yujuan Zhao; Cheng Sun (International Journal of Remote Sensing, 2025)

The instabilities of the Antarctic slope current in an idealized model - Chengyan Liu; Zhaomin Wang; Xi Liang; Xiang Li; Xianxian Han; Wenjin Sun; Yang Wu; Xichen Li; Chen Cheng (Journal of Marine Systems, 2025)

Influence of geometric parameters on ejector acoustics and efficiency in ejector refrigeration system - Wenliang Li; Qingyang Han; Cheng Wang; Hailun Zhang; Lei Jia; Lei Wang; Wenxu Sun; Haoyuan Xue (International Journal of Refrigeration, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

How do we create a healthier thermal environment for sleep? A review of sleep thermal comfort and sleep quality - Zhaohan Bai; Yunsong Han; Dian Zhuang; Cheng Sun (Building and Environment, 2025)

STAT3 mediates ECM stiffness-dependent progression in ovarian cancer - Sun Chenchen; Qian Xueqian; Lu Yahui; Yuan Yi; Zhang Hui; Bai Lanning; Cheng Min; Han Yangyang (Molecular and Cellular Biochemistry, 2025)

d-Allulose production via a simplified in vitro multienzyme cascade strategy: Biosynthesis and crystallization - Han Zhang; Zhen Sun; Xinling Du; Qianqian Cheng; Fuchun Ji; Zishen Nie; Julei Zhan; Zhouping Wang; Aitao Li; Irina Delidovich; Yu Xia (Food Bioscience, 2024)

Attenuation by Zhiqiao neohesperidin on dextran sulfate sodium-induced colitis in mice through inhibition of the TLR4/NF-κB pathway - Guijie Li; Xuting Wang; Xingyao Long; Shanshan Chen; Leng Han; Yujiao Cheng; Suyang Chen; Wenwen Liu; Ruizhang Feng; Zhigao Sun (Food Bioscience, 2024)

A PVA/g-C3N4 nano antibacterial paper to preservation of fresh pork - Zhenlei Yuan; Chenfeng Han; Binqing Sun; Shuqian Cheng; Zechuan Yang; Yuqi Huang (Food Bioscience, 2024)

Corrigendum to “Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor” [Environ. Res. 231 (2023) 116061] - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Influence of beeswax-based fish oil oleogels on the mechanism of water and oil retention in Pacific white shrimp (Litopenaeus vannamei) meat emulsion gels: Filling, emulsification and phase transition - Zongyuan Han; Kaixing Cheng; Yanmo Pan; Fei Chen; Jun-Hua Shao; Shucheng Liu; Qinxiu Sun; Shuai Wei; Hongwu Ji (Food Chemistry, 2024)

Migration of membrane fouling with minimal damage to cell integrity by catalytic ceramic membrane systems in low dosages of ozone during algae-laden water treatment - Dan Song; Xiaodie Han; Jiahui Li; Wei Cheng; Caihong Liu; Chuandong Wu; Jie Qiu; Jun Ma; Zhiqiang Sun (Chemical Engineering Journal, 2024)

Loss of TET Activity in the Postnatal Mouse Brain Perturbs Synaptic Gene Expression and Impairs Cognitive Function - Ji-Wei Liu; Ze-Qiang Zhang; Zhi-Chuan Zhu; Kui Li; Qiwu Xu; Jing Zhang; Xue-Wen Cheng; Han Li; Ying Sun; Ji-Jun Wang; Lu-Lu Hu; Zhi-Qi Xiong; et al. (Neuroscience Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Design, modeling and optimization of an adhesively bonded ring joint with U-section for ceramic cylindrical pressure hull of deep-sea underwater vehicles - Faliang Lu; Yuhong Liu; Tongshuai Sun; Libing Han; Peng Wang; Wendong Niu; Cheng Wang; Lianhong Zhang (Ocean Engineering, 2024)

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

The underlying mechanism between emulsification stability and in vitro digestion in golden pompano (Trachinotus ovatus) myofibrillar protein-fish oil oleogel emulsion under ultrasonic treatments - Yanmo Pan; Shucheng Liu; Zongyuan Han; Liping Shen; Wei Lan; Jun-Hua Shao; Kaixing Cheng; Yang Liu; Qiuyu Xia; Zefu Wang; Qinxiu Sun; Shuai Wei (Food Hydrocolloids, 2024)

Na+ orientates Jahn-Teller effect to tune Li+ diffusion pathway and kinetics for Single-Crystal Ni-rich LiNixCoyMn1-x-yO2 cathode materials - Jiyuan Jian; Xing Xu; Xiaoyi Pan; Guokang Han; Rang Xiao; Ziwei Liu; Dandan Sun; Xin Zhang; Qingjie Zhou; He Zhu; Geping Yin; Hua Huo; et al. (Chemical Engineering Journal, 2024)

Engineered biochar with ultrahigh surface areas derived from postpyrolysis with urea for efficient removal of plasticizer - Gang Ji; Yuxin Hou; Yu Zhang; Zhangxiong Han; Qian Sun; Rongting Ji; Ziyan Li; Jiangang Han; Hu Cheng; Yang Song; Jianming Xue (Fuel, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Co-exposure of decabromodiphenyl ethane and cadmium increases toxicity to earthworms: Enrichment, oxidative stress, damage and molecular binding mechanisms - Zhihua Qiao; Xinlin Sun; Mengru Fu; Shanqi Zhou; Yanna Han; Xuan Zhao; Kailin Gong; Cheng Peng; Wei Zhang; Fang Liu; Chunmei Ye; Jie Yang (Journal of Hazardous Materials, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Luxury application of biochar does not enhance rice yield and methane mitigation: a review and data analysis - Husna Israt Pia; Nuri Baek; Seo-Woo Park; Eun-Seo Shin; Sun-Il Lee; Han-Yong Kim; Shuirong Tang; Weiguo Cheng; Jin-Hyeob Kwak; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2024)
Purpose It is unclear whether a higher biochar (BC) application rate enhances rice ( Oryza sativa L.) yield and reduces CH 4 emissions. This study investigated changes in rice yield and CH 4 emissions with varying BC application rates. Methods Data on rice yield and CH 4 emission from paddies amended with or without BC were collected from the literature, and the biochar effects were analyzed using the data set. Results Across the biochar application rate from 2 to 48 t ha -1 , the rice yield increased (by 10.8%) while the area-scaled (by 14.4%) and yield-scaled CH 4 emission (by 22.2%) decreased. However, the correlation of BC application rates with rice yield and CH 4 mitigation was not significant, implying that a higher BC application rate did not enhance rice yield and CH 4 reduction. Interestingly, for a data set showing increased rice yield and decreased CH 4 emission by BC, the magnitude of change in the rice yield and CH 4 mitigation per unit weight of BC (1 t ha -1 ) decreased with an increase in the BC application rate. These results suggest that BC effects on rice yield and CH 4 mitigation are not additive, probably because of the decreases in the inherent capacity of unit weight of BC to enhance rice yield and reduce CH 4 emission, which might be caused by the adverse effects of toxic compounds contained in BC, losses of BC, and a higher degree of nutrient immobilization by BC. Conclusions Annual BC application at a low rate (e.g., 2 t ha -1 ) rather than a luxury application may be an effective and economical strategy for long-term rice yield enhancement and CH 4 mitigation using BC.

Predicting the bioavailability of polycyclic aromatic hydrocarbons in rhizosphere soil using a new novel in situ solid-phase microextraction technique - Hu Cheng; Qian Sun; Yongrong Bian; Jiangang Han; Xin Jiang; Jianming Xue; Yang Song (Science of The Total Environment, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Algae-bacteria consortia promotes the cell growth of marine microalgae Phaeodactylum tricornutum and Chrysotila roscoffensis - Jiaqi Fang; Yan Sun; Zhujun Zhu; Jian Li; Pengfei Cheng; Spiros N. Agathos; Yuanyuan Fu; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

The association between blue light exposure and incidence of type 2 diabetes: A prospective study of UK biobank - Cheng Wang; Yang Zhao; Qianqi Hong; Yating Lei; Shengyuan Wang; Weiqi Wang; Wei Wei; Changhao Sun; Tianshu Han (Environmental Research, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Spatial distribution prediction of soil heavy metals based on sparse sampling and multi-source environmental data - Yongqiao Sun; Shaogang Lei; Yibo Zhao; Cheng Wei; Xingchen Yang; Xiaotong Han; Yuanyuan Li; Jianan Xia; Zhen Cai (Journal of Hazardous Materials, 2024)

Exploring the factors influencing the low temperature CO gas production characteristics of low-metamorphic coal - Lulu Sun; Huaian Han; Weimin Cheng; Haishan Wang; Quanlin Shi; Guansheng Qi; Zhiguo Guo (Fuel, 2024)

Microbial exopolysaccharide EPS66A inducing walnut (Juglans regia) resistance to bacterial blight - Hao Wu; Yubo Sun; Lan Ma; Siying Cheng; Dianwen Lv; Jianjun Hao; Lirong Han (Food Chemistry, 2024)

Comamonas-dominant microbial community in carbon poor aquitard sediments revealed by metagenomic-based growth rate investigation - Miao Zhang; Bixi Zhao; Yuxi Yan; Zhanwen Cheng; Zengyi Li; Long Han; Yuqin Sun; Yan Zheng; Yu Xia (Science of The Total Environment, 2024)

A sight of self-assembly mechanism in fish oil oleogels: Phase transition, crystal structure and non-covalent interaction - Kaixing Cheng; Yanmo Pan; Zongyuan Han; Zefu Wang; Qinxiu Sun; Shuai Wei; Qiuyu Xia; Yang Liu; Shucheng Liu; Jun-Hua Shao (Food Chemistry, 2024)

Map-based cloning and functional analysis of a major quantitative trait locus, BolC.Pb9.1, controlling clubroot resistance in a wild Brassica relative (Brassica macrocarpa) - Xiaoli Zhang; Fengqing Han; Zhansheng Li; Zhenghua Wen; Wenjuan Cheng; Xiaozheng Shan; Deling Sun; Yumei Liu (Theoretical and Applied Genetics, 2024)

Microalgal protein for sustainable and nutritious foods: A joint analysis of environmental impacts, health benefits and consumer’s acceptance - Shufang Yang; Yuxin Wang; Jia Wang; Kawing Cheng; Jin Liu; Yongjin He; Yifeng Zhang; Haijin Mou; Han Sun (Trends in Food Science & Technology, 2024)

Relative role of soil nutrients vs. carbon availability on soil carbon mineralization in grassland receiving long-term N addition - Liangchao Jiang; Huanhuan Cheng; Yang Peng; Tianran Sun; Yingzhi Gao; Ruzhen Wang; Yanxia Ma; Junjie Yang; Qiang Yu; Haiyang Zhang; Xingguo Han; Qiushi Ning (Soil and Tillage Research, 2024)

Sodium nitroprusside (SNP) treatment increases the postharvest resistance of apple fruit to Alternaria alternata by enhancing antioxidant enzyme activity - Jie Han; Yingying Fan; Tao Sun; Jing An; Yu Ding; Weiwei Zhang; Fengjuan Liu; Cheng Wang (Physiological and Molecular Plant Pathology, 2024)

Toxicity of decabromodiphenyl ethane on lettuce: Evaluation through growth, oxidative defense, microstructure, and metabolism - Zhihua Qiao; Xinlin Sun; Kailin Gong; Xiuping Zhan; Kailun Luo; Mengru Fu; Shanqi Zhou; Yanna Han; Yuyou He; Cheng Peng; Wei Zhang (Environmental Pollution, 2023)

Effects of PM2.5 emissions from household fuel combustion on biomarkers and pulmonary function in rural areas of Fenwei Plain, China - Rong Feng; Hongmei Xu; Hongwei Lu; Bei Han; Yue Cheng; Yunxuan Gu; Jian Sun; Liu Yang; Zhenxing Shen; Junji Cao (Atmospheric Pollution Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Nitrogen addition increased soil particulate organic carbon via plant carbon input whereas reduced mineral−associated organic carbon through attenuating mineral protection in agroecosystem - Tao Sun; Xiali Mao; Kefeng Han; Xiangjie Wang; Qi Cheng; Xiu Liu; Jingjie Zhou; Qingxu Ma; Zhihua Ni; Lianghuan Wu (Science of The Total Environment, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Biofortification of health-promoting glucosinolates in cruciferous sprouts along the whole agro-food chain - Mengyu Wang; Yubo Li; Yuhe Yang; Han Tao; Ghazala Mustafa; Fanliang Meng; Bo Sun; Jiansheng Wang; Yanting Zhao; Fen Zhang; Kejun Cheng; Qiaomei Wang (Trends in Food Science & Technology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Highly efficient zinc electrode prepared by electro-deposition in a salt-induced pre-phase separation region solution - Yaoyu Yin; Yaguang Peng; Meng Zhou; Pei Zhang; Yingying Cheng; Peng Chen; Xueqing Xing; Xiaoxue Ma; Qinggong Zhu; Xiaofu Sun; Qingli Qian; Xinchen Kang; et al. (Science Bulletin, 2023)

Estimating water pollution and economic cost embodied in the mining industry: An interprovincial analysis in China - Han Sun; Xueyuan Hu; Xiaohui Yang; Hai Wang; Jinhua Cheng (Resources Policy, 2023)

Diatomite-Trichoderma viride composite microspheres for selective removal of anionic dyes and copper ions - Shuang Xu; Yunqing Luo; Zhanlian Han; Tong Zhang; Lianzhi Sun; Gaonan Zheng; Keying Wang; Zhiqiang Cheng (Journal of Water Process Engineering, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Optimal design of a glider array for the observation of tropical cyclones - Yutong Sun; Dan Cheng; Shaoqiong Yang; Chenyi Luo; Di Tian; Han Zhang; Yanhui Wang (Progress in Oceanography, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Knockdown of klotho Leads to Cell Movement Impairment during Zebrafish Gastrulation - Heng-Chih Pan; Kang-Chieh Lo; Yun-Hsin Wang; Han-Ting Huang; Shu-Chun Cheng; Chiao-Yin Sun; Yau-Hung Chen (Fishes, 2023)
(1) Background: Klotho is a multifunctional protein, but its biophysiological roles during fish early development are unclear. (2) Methods: We carried out anti-sense Klotho morpholino injection and whole-mount in situ hybridization experiments in this study. (3) Results: Our results showed that in the Klotho MO1-injected group, embryos displayed longitudinal shapes and swelling yolks compared to those of the un-injected groups. Their length/width ratio by 9 hpf for the uninfected group is 1 ± 0.1; but for 0.1 mM-, 0.2 mM-, and 0.5 mM-MO-injected are 1.1 ± 0.1, 1.2 ± 0.1, and 1.3 ± 0.1, respectively, suggesting that the klotho knockdown-induced length/width ratio changes are in a dose-dependent manner. Whole-mount in situ hybridization showed that several cell migration-related gene expressions, including goosecoid, floating head, bone morphogenetic protein 4, and even-skipped-liked 1 were affected in the Klotho MO-injected embryos. (4) Conclusions: We suggest that knockdown of klotho leads to cell movement impairment during zebrafish gastrulation.

Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2023)

Targeting Peripheral μ-opioid Receptors or μ-opioid Receptor-Expressing Neurons Does not Prevent Morphine-induced Mechanical Allodynia and Anti-allodynic Tolerance - Feng Du; Guangjuan Yin; Lei Han; Xi Liu; Dong Dong; Kaifang Duan; Jiantao Huo; Yanyan Sun; Longzhen Cheng (Neuroscience Bulletin, 2023)

Response of rice yield to organic amendments was regulated by soil chemical properties, microbial functional genes and bacterial community rather than fungal community - Tao Sun; Xiali Mao; Qingxu Ma; Kefeng Han; Xiangjie Wang; Qi Cheng; Xiongchao Sheng; Wenhai Mi; Lianghuan Wu (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Cabernet sauvignon dry red wine ameliorates atherosclerosis in mice by regulating inflammation and endothelial function, activating AMPK phosphorylation, and modulating gut microbiota - Xinlong Cheng; Xue Han; Liangfu Zhou; Yasai Sun; Qian Zhou; Xuan Lin; Zhe Gao; Jie Wang; Wen Zhao (Food Research International, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Adenosine triphosphate induced transition-metal phosphide nanostructures encapsulated with N, P-codoped carbon toward electrochemical water splitting - Peng Wei; Xueping Sun; Zhimin He; Fangyuan Cheng; Jia Xu; Qing Li; Yurong Ren; Jianhua He; Jiantao Han; Yunhui Huang (Fuel, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

AIseed: An automated image analysis software for high-throughput phenotyping and quality non-destructive testing of individual plant seeds - Keling Tu; Weifeng Wu; Ying Cheng; Han Zhang; Yanan Xu; Xuehui Dong; Mang Wang; Qun Sun (Computers and Electronics in Agriculture, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Formation of ferritin-agaro oligosaccharide-epigallocatechin gallate nanoparticle induced by CHAPS and partitioned by the ferritin shell with enhanced delivery efficiency - Rui Yang; Junrui Ma; Jiangnan Hu; Haili Sun; Yu Han; Demei Meng; Zhiwei Wang; Lei Cheng (Food Hydrocolloids, 2023)

One-step high-value conversion of heavy oil into H2, C2H2 and carbon nanomaterials by non-thermal plasma - Zhe Fan; Hao Sun; Liguang Dou; Shuai Zhang; Wei Han; Cheng Zhang; Tao Shao (Chemical Engineering Journal, 2023)

Variation of Organic Matter and Releasing Risk Assessment of Pentachlorophenol (PCP) in Sewage Sludge Composting - Guanghuan Cheng; Xiaoyue Zhang; Jiaping Li; Xucheng Han; Feng Li; Mingyang Sun (Water, Air, & Soil Pollution, 2023)

Effect of PVC microplastics on soil microbial community and nitrogen availability under laboratory-controlled and field-relevant temperatures - Hangru Shen; Yuhan Sun; Hongbing Duan; Jinliu Ye; Aoyu Zhou; Han Meng; Fengxiao Zhu; Huan He; Cheng Gu (Applied Soil Ecology, 2023)

Sedimentary spatial variation, source identification and ecological risk assessment of parent, nitrated and oxygenated polycyclic aromatic hydrocarbons in a large shallow lake in China - Jijie Kong; Mengshu Han; Xiaoyu Cao; Xinying Cheng; Shaogui Yang; Shiyin Li; Cheng Sun; Huan He (Science of The Total Environment, 2023)

Autochthonous Bacillus subtilis and Enterococcus faecalis improved liver health, immune response, mucosal microbiota and red-head disease resistance of yellow drum (Nibea albiflora) - Xi-Yue Ding; Cheng-Ye Wei; Zi-Yan Liu; Hong-Ling Yang; Fang Han; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Evaluation of the distribution and mobility of labile phosphorus in sediment profiles of Lake Nansi, the largest eutrophic freshwater lake in northern China - Ye Zheng; Yu Sun; Zhihong Zhang; Chao Han; Zhaode Wang; Cheng Liu; Fan Ke; Lei Zhang; Qiushi Shen (Chemosphere, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Self-activation of potassium/iron citrate-assisted production of porous carbon/porous biochar composites from macroalgae for high-performance sorption of sulfamethoxazole - Jiacheng Qin; Rongting Ji; Qian Sun; Wei Li; Hu Cheng; Jiangang Han; Xin Jiang; Yang Song; Jianming Xue (Bioresource Technology, 2023)

Optimal allocation of water pollutant discharge permits based on Environmental Gini Coefficient (EGC): a case study of Qinhuai river basin in Nanjing, China - Bei Guan; Xiuqiong Liang; Yang Yang; Xiang Sun; Jiawei Wang; Danyi Wei; Bin Wang; Han Cheng (Environment, Development and Sustainability, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Evaluation of the inhibitory effects of four different microecological preparations on Cladophora - Jian Liu; Yunfei Sun; Wenfeng Han; Jinghao Li; Shihui Wang; Zhigang Yang; Yongxu Cheng (Aquaculture International, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Characterization of a new gene for resistance to wheat powdery mildew on chromosome 1RL of wild rye Secale sylvestre - Huagang He; Haonan Du; Renkang Liu; Tianlei Liu; Lijun Yang; Shuangjun Gong; Zongxiang Tang; Haimei Du; Cheng Liu; Ran Han; Weihong Sun; Lei Wang; et al. (Theoretical and Applied Genetics, 2021)

Polybrominated diphenyl ethers in soils from Tianjin, North China: distribution, health risk, and temporal trends - Yu Han; Jiali Cheng; Lei He; Minna Zhang; Shan Ren; Jiazheng Sun; Xiangyang Xing; Zhenwu Tang (Environmental Geochemistry and Health, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Changes in arthropod community but not plant quality benefit a specialist herbivore on plants under reduced water availability - Po-An Lin; Chia-Ming Liu; Jia-Ang Ou; Cheng-Han Sun; Wen-Po Chuang; Chuan-Kai Ho; Natsuko Kinoshita; Gary W. Felton (Oecologia, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

The short-term effect of PM2.5/O3 on daily mortality from 2013 to 2018 in Hefei, China - Xinmiao Sui; Junqing Zhang; Qi Zhang; Shu Sun; Ruoqian Lei; Chao Zhang; Han Cheng; Liu Ding; Rui Ding; Changchun Xiao; Xiaoru Li; Jiyu Cao (Environmental Geochemistry and Health, 2021)

Enhancing Salix viminalis L.–mediated phytoremediation of polycyclic aromatic hydrocarbon–contaminated soil by inoculation with Crucibulum laeve (white-rot fungus) - Xiaodong Ma; Xia Li; Junxiang Liu; Yunhe Cheng; Feifei Zhai; Zhenyuan Sun; Lei Han (Environmental Science and Pollution Research, 2020)

Molecular cloning and characterization of a gene encoding soluble starch synthase III (SSSIII) in Lotus (Nelumbo nucifera) - FengLin Zhu; Neng Cheng; Han Sun; Ying Diao; Zhongli Hu (Biologia, 2020)

Crocin attenuates isoprenaline-induced myocardial fibrosis by targeting TLR4/NF-κB signaling: connecting oxidative stress, inflammation, and apoptosis - Weiyue Jin; Yuanyuan Zhang; Yurun Xue; Xue Han; Xuan Zhang; Zhihong Ma; Shijiang Sun; Xi Chu; Jie Cheng; Shengjiang Guan; Ziliang Li; Li Chu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Orientin Improves Cognition by Enhancing Autophagosome Clearance in an Alzheimer’s Mouse Model - Yi Zhong; Qing-yu Zheng; Cheng-yan Sun; Ze Zhang; Kun Han; Ning Jia (Journal of Molecular Neuroscience, 2019)

Biological properties and genomics analysis of vB_KpnS_GH-K3, a Klebsiella phage with a putative depolymerase-like protein - Ruopeng Cai; Zijing Wang; Gang Wang; Hao Zhang; Mengjun Cheng; Zhimin Guo; Yalu Ji; Hengyu Xi; Xinwu Wang; Yibing Xue; Sadeeq ur Rahman; Changjiang Sun; et al. (Virus Genes, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

Crack propagation and hydraulic fracturing in different lithologies - Zhen-Kun Hou; Han-Lie Cheng; Shu-Wei Sun; Jun Chen; Dian-Qing Qi; Zhi-Bo Liu (Applied Geophysics, 2019)

Activities and conformation changes of food enzymes induced by cold plasma: A review - Yongxu Han; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

A quantum theory investigation on atmospheric oxidation mechanisms of acrylic acid by OH radical and its implication for atmospheric chemistry - Han Chu; Wenzhong Wu; Youxiang Shao; Yizhen Tang; Yunju Zhang; Yinfang Cheng; Fang Chen; Jiangyan Liu; Jingyu Sun (Environmental Science and Pollution Research, 2018)

Next-generation sequencing reveals genetic landscape in 46, XY disorders of sexual development patients with variable phenotypes - Hao Wang; Lele Zhang; Nan Wang; Hui Zhu; Bing Han; Feng Sun; Haijun Yao; Qiang Zhang; Wenjiao Zhu; Tong Cheng; Kaixiang Cheng; Yang Liu; et al. (Human Genetics, 2018)

iTRAQ-based comparative proteomic analysis provides insights into somatic embryogenesis in Gossypium hirsutum L. - Hua-Guo Zhu; Wen-Han Cheng; Wen-Gang Tian; Yang-Jun Li; Feng Liu; Fei Xue; Qian-Hao Zhu; Yu-Qiang Sun; Jie Sun (Plant Molecular Biology, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Biological Decolorization and Degradation of Malachite Green by Pseudomonas sp. YB2: Process Optimization and Biodegradation Pathway - Yanbin Tao; Fei Wang; Lingjun Meng; Yang Guo; Mengshu Han; Jinhai Li; Cheng Sun; Shaomang Wang (Current Microbiology, 2017)

The effect of Mg2+ on digestion performance and microbial community structures in sludge digestion systems - CongCong Liu; Cheng Huang; XiuYun Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Lianjun Wang (Environmental Science and Pollution Research, 2017)

Genome-wide identification and expression analysis of polyamine oxidase genes in upland cotton (Gossypium hirsutum L.) - Xin-Qi Cheng; Xue-Feng Zhu; Wen-Gang Tian; Wen-Han Cheng; Hakim; Jie Sun; Shuang-Xia Jin; Hua-Guo Zhu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Safety Evaluation of Sevoflurane as Anesthetic Agent in Mouse Model of Myocardial Ischemic Infarction - Xiang Cheng; Jianglong Hou; Jiaming Liu; Xiaorong Sun; Qin Sheng; Pengfei Han; Y. James Kang (Cardiovascular Toxicology, 2017)

Bioaugmentation of a continuous-flow self-forming dynamic membrane bioreactor for the treatment of wastewater containing high-strength pyridine - Cheng Hou; Jinyou Shen; Dejin Zhang; Yi Han; Dehua Ma; Xiuyun Sun; Jiansheng Li; Weiqing Han; Lianjun Wang; Xiaodong Liu (Environmental Science and Pollution Research, 2017)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

De novo transcriptome analysis reveals insights into dynamic homeostasis regulation of somatic embryogenesis in upland cotton (G. hirsutum L.) - Wen-Han Cheng; Hua-Guo Zhu; Wen-Gang Tian; Shou-Hong Zhu; Xian-Peng Xiong; Yu-Qiang Sun; Qian-Hao Zhu; Jie Sun (Plant Molecular Biology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Toxic effects of HT-2 toxin on mouse oocytes and its possible mechanisms - Cheng-Cheng Zhu; Yue Zhang; Xing Duan; Jun Han; Shao-Chen Sun (Archives of Toxicology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Hydrolysis and volatile fatty acids accumulation of waste activated sludge enhanced by the combined use of nitrite and alkaline pH - Cheng Huang; Congcong Liu; Xiuyun Sun; Yinglu Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Xiaodong Liu; Lianjun Wang (Environmental Science and Pollution Research, 2015)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Transcriptional regulatory network and protein–protein interaction to reveal the mechanism of pancreatic cancer - Hongli Sun; Bing Han; Xinhua Cheng; Kai Ma (Molecular Biology Reports, 2014)

Distinct Expression of Mas1-Related G-Protein-Coupled Receptor B4 in Dorsal Root and Trigeminal Ganglia—Implications for Altered Behaviors in Acid-Sensing Ion Channel 3-Deficient Mice - Ya-Han Huang; Chin-Yu Chang; Chih-Cheng Chen; Chih-Dong Yang; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2013)

Fruit skin color and the role of anthocyanin - Emrul Kayesh; Lingfei Shangguan; Nicholas Kibet Korir; Xin Sun; Nadira Bilkish; Yanping Zhang; Jian Han; Changnian Song; Zong-Ming Cheng; Jinggui Fang (Acta Physiologiae Plantarum, 2013)

Inhibition of hydrogen sulfide synthesis provides protection for severe acute pancreatitis rats via apoptosis pathway - Gang Wang; Bing Han; Haoxin Zhou; Linfeng Wu; Yongwei Wang; Guang Jia; Jiachen Lv; Zhuoxin Cheng; Shangha Pan; Ji Liu; Yinan Zhou; Bei Sun (Apoptosis, 2013)

Selecting the optimum location of the corner using gravity gradient method - Peng-Fei Sun; Yan-Gang Wu; Chun-Cheng Yang; Zhao-Hong Han; Mei-Ning Fan (Applied Geophysics, 2011)

cDNA sequence and tissues expression analysis of lipoprotein lipase from common carp (Cyprinus carpio Var. Jian) - Han-liang Cheng; Si-ping Sun; Yong-xing Peng; Xiao-yun Shi; Xin Shen; Xue-ping Meng; Zhi-guo Dong (Molecular Biology Reports, 2010)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)